Study of corrosion behavior of arc thermal sprayed Al-Mg alloy coating - Pham Thi, Ha; Nguyen Van, Tuan; Nguyen, Tuan Anh; Pham Thi, Ly; Ly Quoc, Cuong; Dao Bich, Thuy; Vo An, Quan (Vietnam Journal of Science and Technology, 2023)
In this study, Al-Mg alloy coatings were deposited on a C45 steel substrate by using the electric arc spray technique. The corrosion behavior of the coating was studied by electrochemical measurements and salt spray tests. The electrochemical tests were performed in 3.5 wt.% NaCl solution. Polarization tests indicated that the corrosion potential of the coating is significantly more negative than that of steel substrate after 240 hours of immersion. EIS measurements showed that after 24 hours of immersion, the total impedance increased with increasing the immersion time. This could be due to sealing of pores by corrosion products which hinder further penetration of the solution through the coating. Red rust spots did not appear on the surface of the coating after 1360 hours of salt spray test. The corrosion rate of the coating decreased with the increase in salt spray test time. After the salt spray test, the coating surface pitted and the cross section of the coating appeared with many long voids. In addition, XRD analysis proved that the main corrosion product was Al(OH)3. The results obtained indicated that arc thermal sprayed Al-Mg alloy coatings can reliably protect steel structures against corrosion in chloride-containing aqueous solutions.